2006
DOI: 10.1073/pnas.0509196103
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Leishmania major in macrophages and mice requires the gluconeogenic enzyme fructose-1,6-bisphosphatase

Abstract: Leishmania are protozoan parasites that replicate within mature phagolysosomes of mammalian macrophages. To define the biochemical composition of the phagosome and carbon source requirements of intracellular stages of L. major, we investigated the role and requirement for the gluconeogenic enzyme fructose-1,6-bisphosphatase (FBP). L. major FBP was constitutively expressed in both extracellular and intracellular stages and was primarily targeted to glycosomes, modified peroxisomes that also contain glycolytic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
117
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 42 publications
7
117
1
8
Order By: Relevance
“…While the reduced p-STAT2 level in La-infected DCs could reflect the degradation of total STAT2 proteins by the parasites, the mechanisms by which La reduces phosphorylation of STAT1 are not known. Although various types of Leishmania-derived phosphatases, such as LPTP1, bisphosphatase and secreted acid phosphatase, have recently been identified (Naderer et al, 2006;Nascimento et al, 2006), our studies with phosphatase inhibitor (bpV)-pretreated parasites suggested a limited role for parasite-derived phosphatases in the dephosphorylation of STAT1 (Fig.5D). Whether La infection triggers the activation of a host cellular phosphatase(s) awaits further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…While the reduced p-STAT2 level in La-infected DCs could reflect the degradation of total STAT2 proteins by the parasites, the mechanisms by which La reduces phosphorylation of STAT1 are not known. Although various types of Leishmania-derived phosphatases, such as LPTP1, bisphosphatase and secreted acid phosphatase, have recently been identified (Naderer et al, 2006;Nascimento et al, 2006), our studies with phosphatase inhibitor (bpV)-pretreated parasites suggested a limited role for parasite-derived phosphatases in the dephosphorylation of STAT1 (Fig.5D). Whether La infection triggers the activation of a host cellular phosphatase(s) awaits further investigation.…”
Section: Discussionmentioning
confidence: 67%
“…Li ϩ -sensitive phosphatases are putative targets for lithium therapy in the treatment of manic depressive patients (4), whereas FBPases are targets for the development of drugs for the treatment of noninsulindependent diabetes (5,6). In addition, FBPase is required for virulence in Mycobacterium tuberculosis and Leishmania major and plays an important role in the production of lysine and glutamate by Corynebacterium glutamicum (7,8).…”
mentioning
confidence: 99%
“…The ability of these glucogenic precursors to promote synthesis of polysaccharides argues that a bona fide gluconeogenic pathway exists in Leishmania parasites. Furthermore, a recent study (40) reveals that this pathway is essential for the survival of amastigotes of L. major, because a null mutant in the gene encoding the gluconeogenic enzyme FBPase is not viable in the amastigote stage of the life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Naderer et al (40) has demonstrated that a null mutant (⌬fbp) in the gene encoding the gluconeogenic enzyme FBPase in L. major is also unable to survive as amastigotes, and in this regard, has a phenotype quite similar to that of the glucose transporter null mutant. Together, these results underscore the importance of carbohydrates in amastigotes and imply that the intracellular stage of the life cycle requires both glucose transporters and gluconeogenesis for viability.…”
Section: Sugar Repletementioning
confidence: 99%